Operations management for healthcare - Vissers, Jan; Elkhuizen, Sylvia; Proudlove, Nathan (Abingdon, Oxon ; New York, NY : Routledge, 2023)
This fully updated edition of the bestselling textbook on Health Service Operations Management provides an invaluable reference for students and researchers in the fields of healthcare management, operations management and patient flow logistics. Featuring theoretical frameworks and a comprehensive set of practical case studies, this book also covers subjects such as hospital planning and supply chain management in healthcare, quality assurance and performance management. Healthcare managers work together with healthcare professionals in a multitude of challenging scenarios. Trade-offs have to be made between waiting times for customers and efficient use of scarce resources, between quality of care and quality of services, between the perspective of a single pathway and the total system, and between the perspective of a single provider and that of a network of providers working together in the chain of primary care, hospitals, nursing homes and home care. This book guides healthcare students and professionals through a set of practical tools and resources, ranging from simple queueing models to more complicated analytical models, to help address these issues. The book can be used at an undergraduate level by introducing concepts, definitions and approaches, and at a postgraduate level through the application of approaches to operations management problems in healthcare practice. It will serve as a primary textbook for a health service operations management course module in a Master's program on healthcare management.
Revised edition of: Health operations management / Jan Vissers and Roger Beech. 2005.
OCLC-licensed vendor bibliographic record.
Keywords: Health services administration -- Textbooks; Hospitals -- Administration -- Textbooks; Operations research -- Textbooks; MEDICAL / Administration; MEDICAL / Health Care Delivery; BUSINESS & ECONOMICS / Management